Kejanggalan Impeachment Kepala Daerah di Era Pemilihan Langsung - aziz hakim (Fakultas Hukum Universitas Islam Indonesia, 2011)
The focus of this research is on the conformity of head of local government impeachment mechanism regulated in Act No. 32 of 2004 and Act No. 12 of 2008 with direct democracy system and the impeachment mechanism of head of local government in Indonesia after the enactment of Act No. 32 of 2004 and Act No. 12 of 2008.This research used normative juridical approach by focusing on philosophical approach. To complete the research matters, primary, secondary and tertiary legal matters method is used. The legal materials are qualitatively analyzed.The research result concludes that impeachment of kepala daerah in direct democracy era needs to be re-designed because it is not in accordance with concept of regional autonomy and the principles of legislation formation. On top of that it is to avoid centralistic system which is contradicted with the essence of decentralist system and not in line with decentralization values in the context of unitary in impeachment system.